2006
DOI: 10.1016/j.chemosphere.2005.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Serum polychlorinated biphenyl and organochlorine insecticide concentrations in a Faroese birth cohort

Abstract: The objective of this study was to assess blood concentrations of polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs), and their polychlorobiphenylol (OH-PCB) metabolites in humans with a high seafood intake. Samples were obtained from pregnant women in the Faroe Islands in 1994-1995 and from their children at 7 years of age to examine maternal transfer of the compounds to their child, age-dependent metabolism, and temporal changes. Maternal serum was dominated by 2,2',4,4'-tetrabromodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…First of all, the biological half-lives of many of these compounds are counted in decades (Hagmar et al ., 2006). Moreover, studies in a Faroese birth cohort demonstrated strong intra-individual correlations between persistent chemicals in cord blood and serum concentrations at 7 and 14 years of age, respectively (Barr et al ., 2006). Another study found high correlations of persistent chemical levels in serum samples in adult men obtained up to 10 years apart (Hagmar et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the biological half-lives of many of these compounds are counted in decades (Hagmar et al ., 2006). Moreover, studies in a Faroese birth cohort demonstrated strong intra-individual correlations between persistent chemicals in cord blood and serum concentrations at 7 and 14 years of age, respectively (Barr et al ., 2006). Another study found high correlations of persistent chemical levels in serum samples in adult men obtained up to 10 years apart (Hagmar et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The serum fraction was separated and a 1-mL aliquot was taken for analysis. Samples were spiked with isotopically labeled p , p ′–DDT and p , p ′–DDE analogs, homogenized, denatured and extracted in Costa Rica using a slight modification of the method of Barr et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Other methods for analysis of serum extracts include mass spectrometry (MS) [50][51][52] and high resolution mass spectrometry with isotope dilution quantification. [53][54][55] These analyses are typically more selective and sensitive than GC-ECD analyses; however, the high cost of instrumentation and isotopically labeled standards and the complex operation and maintenance of these instruments often preclude their routine use in many laboratories.…”
Section: Organochlorine Pesticidesmentioning
confidence: 99%
“…One novel method employs an on-line cleanup or supercritical fluid extraction (SFE) and preconcentration followed by separation and analysis using micellar electrokinetic chromatography with UV detection. 65 OC pesticides have been measured in a variety of populations ranging from indigenous or fish eating populations 53,67,68 to the general population. [69][70][71] Concentrations of these pesticides tend to be highest in people who have some continued exposure source such as consumption of foods in which the pesticide has bioaccumulated or in those living in an area endemic to vector-borne disease for which OC pesticides may have been more recently used.…”
Section: Organochlorine Pesticidesmentioning
confidence: 99%